2017
DOI: 10.1002/ghg.1663
|View full text |Cite
|
Sign up to set email alerts
|

Experimental results of split flow process using AMP/PZ solution for post‐combustion CO2 capture

Abstract: The goal of reducing energy consumption of the CO2 removal process from flue gas may be pursued by developing new solvents as well as by modifying the technological process itself. This paper provides a discussion of the experimental results obtained from a process development unit (PDU) using an aqueous 2‐amino‐2‐methyl‐1‐propanol (AMP) solution activated with piperazine (PZ) for post‐combustion carbon capture located at the Clean Coal Technologies Centre in Poland. The results are compared for two distinct p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The semi-lean amine is pumped into the absorber, being introduced near the bottom where the bulk of the absorption occurs. The second split stream is introduced in the down section of the stripper where further CO2 desorption is produced [84].…”
Section: Novel Configurations and Process Integration Into Fossil-fue...mentioning
confidence: 99%
“…The semi-lean amine is pumped into the absorber, being introduced near the bottom where the bulk of the absorption occurs. The second split stream is introduced in the down section of the stripper where further CO2 desorption is produced [84].…”
Section: Novel Configurations and Process Integration Into Fossil-fue...mentioning
confidence: 99%
“…Over the past decades, solvent blends have become of increasing interest to researchers, such as the mixture of 1‐amino‐2‐methyl‐1‐propanol (AMP) and piperazine (PZ) which takes advantage of the high reaction rate of PZ with CO 2 , as well as the high CO 2 loading capacity ( α ) and lower regeneration energy requirement of AMP. This blend has been studied and used in pilot‐scale systems for amine‐based CO 2 removal from flue gas 1,11–22 . This solvent blend has better performance in energy saving than the conventional monoethanolamine (MEA) solvent 17,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two available nitrogen atoms on a PZ molecule means that the rate of CO 2 absorption is faster than that of aqueous MEA. Previous studies on PZ also suggested that its thermal degradation to be limited and PZ regeneration required 10–20% less energy than aqueous MEA. Piperazine has been used with amines such as methyl diethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) to enhance CO 2 absorption and reduce the energy requirement. A recent HYSYS simulation by Hosseini-Ardali et al calculated a regeneration energy of around 2.7 GJ/ton CO 2 for MDEA-PZ solution, which is lower than that of the standard 30 wt % aqueous MEA . In this work, aqueous MEA was blended with PZ as another potential amine solution for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%